Protection Against Expulsion - Wielec, Marcin; Oręziak, Bartłomiej; Starybrat, Julia (The European Convention on Human Rights: A Central and Eastern European Perspective, 2026)
This chapter explores the international legal duties related to the expulsion of individuals, as shaped by Council of Europe standards. It starts by presenting the core principles of international human rights law, paying particular attention to the European Convention on Human Rights (ECHR) and its additional protocols. The discussion focuses on key restrictions, such as the ban on expelling nationals of a country and the prohibition of collective expulsions of foreigners, as well as the procedural guarantees that must be observed during expulsion processes. These aspects are examined not only through the wording of treaty provisions but also in light of the case law of the European Court of Human Rights, which has played a central role in defining the meaning and scope of these safeguards. The chapter then describes how these protections intersect with the principle of nonrefoulement, stressing its absolute nature under Article 3 of the ECHR and based on an analysis of its application in present-day migration contexts. By linking the legal framework with practical mechanisms and recent developments − such as large-scale migration movements and the adoption of the new European Union Pact on Migration and Asylum − the text sheds light on the ongoing tension between state sovereignty and international commitments. The chapter concludes with reflections on the shifting balance between national security concerns and the obligation to protect fundamental rights, offering broader insights into the resilience and adaptability of the European system of human rights protection. Keywords: expulsion of nationals, state sovereignty, collective expulsion, non-refoulement